Marketing Strategy, Product Safety, and Ethical Factors in Consumer Choice - Curlo, Eleonora (Journal of business ethics, 1999)
Firms that wish to be morally responsible in providing products that meet a high standard of safety may face problems competing against firms that make unsafe products and sell these products at cheap prices; these problems may be compounded when consumers do not accurately process information about safety and risk. This paper presents a conceptual argument that the tort system may serve to promulgate information which makes it feasible for firms to market safe products even in the face of these competitive obstacles., To corroborate the conceptual argument, the paper presents the results of an experimental study about the impact of negligence liability information on consumer product safety evaluation. The results show that provision of negligence information heightens consumer concern for safety and firms' ethical behavior, and increases the proportion of consumer choices in favors of the brands sold by manufacturers with a favorable track record for quality. More importantly, they indicate that provision of negligence information reduces the likelihood that brands which conform to inferior safety standards will be chosen by consumers who care about safety standards.